2020
DOI: 10.3389/fgene.2020.607558
|View full text |Cite
|
Sign up to set email alerts
|

A Major QTL for Resistance to Vibrio anguillarum in Rainbow Trout

Abstract: Genetic selection of disease resistant fish is a major strategy to improve health, welfare and sustainability in aquaculture. Mapping of single nucleotide polymorphisms (SNP) in the fish genome may be a fruitful tool to define relevant quantitative trait loci (QTL) and we here show its use for characterization of Vibrio anguillarum resistant rainbow trout (Oncorhynchus mykiss). Fingerlings were exposed to the pathogen V. anguillarum serotype O1 in a solution of 1.5 × 107 cfu/ml and observed for 14 days. Diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 78 publications
4
29
0
Order By: Relevance
“…The early infection (3 dpc) triggered a strong transcriptional up-regulation of many immune genes in different organs including those encoding pro-inflammatory cytokines IL-1β, IL-6 and TNFα and other cytokines involved in the development of adaptive immunity (IL-8, IL-10, IL-22, IL-17C2, INFγ). The clear up-regulation of previously mentioned immune markers is consistent with earlier studies in trout exposed to A. salmonicida 47,52,53 and other bacterial pathogens 12,35 . Along with the inflammation induced we saw a marked up-regulation of SAA, C3 and several other components of the innate immune system (lysozyme and cathelicidins).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The early infection (3 dpc) triggered a strong transcriptional up-regulation of many immune genes in different organs including those encoding pro-inflammatory cytokines IL-1β, IL-6 and TNFα and other cytokines involved in the development of adaptive immunity (IL-8, IL-10, IL-22, IL-17C2, INFγ). The clear up-regulation of previously mentioned immune markers is consistent with earlier studies in trout exposed to A. salmonicida 47,52,53 and other bacterial pathogens 12,35 . Along with the inflammation induced we saw a marked up-regulation of SAA, C3 and several other components of the innate immune system (lysozyme and cathelicidins).…”
Section: Discussionsupporting
confidence: 90%
“…Fish showing clinical signs (653) were sampled as susceptible and at 13 dpc all fish surviving the challenge (145) were sampled as resistant. For DNA-typing, a circular tissue piece (Ø 2.75 mm) was taken from the tail fin of each fish using punching scissors (AgnTho's AB, Lidingö, Sweden) and transferred to lysis buffer (Vaxxinova Norge, Bergen, Norway) for subsequent DNA purification and genotyping according to Karami et al 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, genes encoding IL-8 (cytokine/ chemokine attracting neutrophils and other leukocytes), cathelicidin 1 and 2 (antimicrobial peptides), lysozyme and complement factors are expressed following Vibrio anguillarum exposure of rainbow trout gills. 15 External environmental factors influence the neutrophil response as temperature is a main regulator of fish physiology due to the poikilothermic nature of this animal group. Some studies have shown a temperature-dependent positive correlation between peripheral blood neutrophil concentrations in Atlantic salmon blood between 10 and 18°C.…”
Section: Regulation Of Neutrophil Responsesmentioning
confidence: 99%
“…A first commercial medium-density Axiom® Trout Genotyping array (hereafter termed 57K chip) has then been developed (Palti et al, 2015) and produced by Affymetrix (Thermofisher). Since then it has been largely used in population genetics studies (Larson et al, 2018; D’Ambrosio et al, 2019; Paul et al, 2021), GWAS and GS accuracy works for various traits in farmed populations (Gonzalez-Pena et al, 2016; Vallejo et al, 2017, 2019; Reis Neto et al, 2019; Rodríguez et al, 2019; Yoshida et al, 2019; Fraslin et al, 2019, 2020; Karami et al, 2020; D’Ambrosio et al, 2020; Blay et al, 2021a, 2021b). However, out of the 57,501 SNPs included in this chip, nearly 20,000 were found to be unusable because they were either duplicated due to the ancestral genome duplication or showing primer polymorphism in 5 French commercial or experimental lines (D’Ambrosio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%